Sports activity of the inhabitants of rural areas - motives for participation in a mass running event on the example of the Poznań Half Marathon - Ewa Malchrowicz-Mośko; Joanna Poczta (Kazimierz Wielki University, 2017)
This article is the result of research conducted during the 6th Half Marathon in Poznan. Its purpose is to know the motivation of participation in Poznan half-marathon among the inhabitants of rural areas, active participants in the race. They are the subject of research analysis. Theoretical basis of the study is a review of the literature on motives of participation in mass running events. The division of Freyer and Gross, who among the motifs of participation in sporting events, distinguished four types of orientation, was the basis for the development of the author's questionnaire survey of motives for participation in running events. The questionnaire served as a research tool and enabled the collection of data.